ANALYSIS OF THE ROLE OF ACTORS IN THE ACTUALIZATION OF THE WOMEN-FRIENDLY AND CHILD-CARE VILLAGE PROGRAM (DRPPA) IN DENPASAR CITY - I Putu Adi Permana Putra; Nyoman Sumawidayani (Jurnal Widya Publika, 2026)
The implementation of the Women-Friendly and Child-Caring Village (DRPPA) program in Denpasar City represents a governance transformation from a centralistic bureaucratic approach to cross-sectoral collaboration. The high complexity of urban social vulnerability demonstrates that top-down interventions are frequently hindered by sectoral egos and the limited capacities of implementers. This study aims to comprehensively analyze the roles of actors, interaction dynamics, and collaborative governance networks in the actualization of DRPPA in Denpasar City. This research employs a qualitative method with a descriptive-analytical approach. Data collection techniques included observation, in-depth interviews, and literature reviews. The informants were selected using the exponential discriminative snowball sampling model. The data analysis technique followed a systematic process: collecting and preparing data for analysis via interview transcripts; reading through the entire data to build a general sense of the information and reflect on its overall meaning; organizing the data; identifying and presenting the data; and developing interpretations to derive meaning from the field research findings. The results indicate that the actualization of DRPPA does not rely on a single entity but is driven by an ecosystem of actor network levels, ranging from macro to micro. The Macro Level is legitimized by the Mayoral Regulation (Perwali) Number 22 of 2023; the Meso Level is realized through the synergy of village governance with the authority of Traditional Village Leaders (Prajuru Desa Adat); while the Micro Level is mobilized by NGOs, SAPA Desa Volunteers, and the Children's Forum as the spearheads of empowerment. The novelty of this research highlights the efforts to integrate the pillar of state law with the cultural pillar of traditional authority through the establishment of customary regulations for the protection of women and children. Furthermore, these findings emphasize a progressive paradigm shift, wherein the Children's Forum transforms from mere objects into active supervisory subjects. The institutionalization of gender-responsive policies is proven to function effectively through the active contributions of the involved actors.